The Influence Of Financial Literacy And Capital Market Training On Investment Decision Making At PT. Fuse Teknologi Indonesia - Ananda Hadistia; Ardi Bachtiar; Indri Kharisma (Jurnal Ekonomi, 2024)
The purpose of this study is to determine the impact of financial literacy and market knowledge on the decision to invest in PT. Fuse Teknologi Indonesia. The method used in this research is a quantitative method. The sampling technique used is called "jenuh sampling," which involves using a sample of fifty-one respondents, or employees of PT. Fuse Teknologi Indonesia. The statistical analysis technique that is used includes the evaluation of validity, reliability, assumption, regression of berganda lines, coefficient of determination, t and f hypotheses. The research findings indicate that the parsial Financial Literacy (X1) has a positive impact and the Partial Investment Decision Making (Y) has a positive impact with a t hitung > t tabel at or (2,237 > 1,677). The parsial Capital Market Training (X2) has a positive impact and a significant effect with respect to the Partial Investment Decision Making (Y) with a t hitung > t tabel.